Evaluation of forequarter, rib and dorsal cuts in culled cows - Jardim, Pedro Osório da Conceição; Guarenti, Noris Maffei; Osório, José Carlos da Silveira (Pesquisa Agropecuaria Brasileira, 2014)
Forty-one carcasses of culled cows were used, averaging eight and a half years. The main objective in the study was to establish the relationship among weight and percentage of forequarter, rib and dorsal cuts with measurements taken on the carcasses. Measurements were: warm carcass weight, conformation, covering fat thickness, leg length, carcass length, deepness, width and area of the longissimus dorsi muscle, weight and percentage of forequarter, rib and dorsal cuts. Main regression equations were: forequarter cut weight = 1.94 + 0.16 (weight of warm carcass), with an r2 = 0.58 (P <0.01); forequarter cut percentage = 37.69 - 2.17 (deepness of longissimus muscle) + 0.72 (width of longissimus muscle), with an r2 = 0.17 (P <0.05); rib cut weight = - 0.27 + 0.06 (warm carcass weight), with an r2 = 0.50 (P <0.01); rib cut percentage = 15.62 - 0.73 (width of longissimus muscle) + 1.23 (deepness of longissimus muscle), with an r2 = 0.20 (P <0.05); dorsal weight = 0.81 + 0.24 (weight of warm carcass), with an r2 = 0.92 (P <0.01) and dorsal percentage = 5.22 + 0.62 (deepness of longissimus muscle) - 2.64 (fat thickness) + 0.01 (warm carcass weight) - 0.09 (leg length), with an r2 = 0.07 (P >0.05). The results permit to conclude: 1. Warm carcass weight is the main measurement to estimate weight of forequarter, rib and dorsal cuts. 2. These carcass measurements do not precisely estimate the percentage of cuts.